Reformasi Pemikiran Islam Modern: Analisis Kritis terhadap Gagasan Muhammad Abduh dan Rashid Ridha dalam Konteks Pendidikan Islam. - tikawaliyahzahrah; Noviasy, Oktha; Alfariz, Syahril Hilman; Syamsul, E Mulya (Al-Akhbar: Jurnal Ilmiah Keislaman, 2025)
The issue of reforming modern Islamic thought has become very relevant in answering the challenges of contemporary Islamic education that faces methodological crises and epistemological stagnation. This research highlights the ideas of Muhammad Abduh and Rasyid Ridho as two main figures of reformist Islamic thought who prioritize rationality, ijtihad and education as instruments of change. Previous research can be seen from the lack of a comparative-critical approach that examines the historical relevance and actuality of thought of both in the context of modern Islamic education. This research answers how the ideas of Muhammad Abduh and Rasyid Ridho are represented and reinterpreted in the current Islamic education system. This study uses a qualitative-descriptive approach with the Literature study method in primary and secondary works. The analysis is carried out through the stages of historical interpretation, contextualization, and conceptual synthesis. The findings of the study show that the modernization of education and the liberation of people's intellect have similarities, there is a difference in methodological approach between Muhammad Abduh who is progressive and Rasyid Ridho who tends to be traditional. This research opens up further studies to develop an adaptive and relevant Islamic education model to the dynamics of the times